High-efficiency perovskite quantum dot solar cells benefiting from a conjugated polymer-quantum dot bulk heterojunction connecting layer. Issue 16 (17th April 2020) - Ji, Kang; Yuan, Jiabei; Li, Fangchao; Shi, Yao; Ling, Xufeng; Zhang, Xuliang; Zhang, Yannan; Lu, Huiyu; Yuan, Jianyu; Ma, Wanli
Abstract : Through constructing polymer-quantum dot bulk heterojunction interfaces, we reported efficient CsPbI3 and FAPbI3 perovskite quantum dot solar cells. Abstract : In this work, we reported an efficient and universal method to fabricate perovskite quantum dot (PQD) solar cells with enhanced efficiency. Through dissolving an optimal amount of conjugated polymers in a PQD matrix solution to fabricate a polymer-QD bulk heterojunction hybrid layer located at PQD/hole transporting layer (HTL) interfaces, the resultant solar cell devices exhibit significantly enhanced short-circuit current density and efficiency. In-depth characterization indicates that adding an optimal amount of conjugated polymers to the PQD film can effectively reduce pin-holes, resulting in more efficient interfacial charge transfer and decreased carrier recombination loss. More importantly, it shows that the highest occupied molecular orbital (HOMO) energy level of the conjugated polymer is crucial for achieving improved carrier transport at the PQD/HTL interfaces. Through rational selection of conjugated polymers, we achieved the best power conversion efficiency of ∼14% and 13.2% for CsPbI3 and FAPbI3 PQD based solar cells respectively, placing them at the forefront of all reported PQD solar cells. These findings will provide insights into well controlling organic–inorganic interfaces to improve current PQD based photovoltaic (PV) devices.